2011
DOI: 10.1121/1.3605671
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of local vocal fold deformation characteristics in an in vitro static tensile test

Abstract: Voice quality is strongly dependent on vocal fold dynamics, which in turn are dependent on lung pressure and vocal fold biomechanics. Numerical and physical models are often used to investigate the interactions of these different subsystems. However, the utility of numerical and physical models is limited unless appropriately validated with data from physiological models. Hence a method that enables analysis of local vocal fold deformations along the entire surface is presented. In static tensile tests, forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…2 and Miri et al, 2013), and human NLSM results (Miri et al, 2012c) suggests that porcine VFs are much less differentiated than human VFs. The special homogeneity of VF tissue along anterior–posterior direction was subject of pervious research (Dollinger et al, 2011; Kelleher et al, 2010). Similar to our results, point force excitations (Dollinger et al, 2011) showed that stiffness increases from the central region to the cartilaginous anterior– posterior ends for human tissue, in contrast with those of tensile test (Kelleher et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and Miri et al, 2013), and human NLSM results (Miri et al, 2012c) suggests that porcine VFs are much less differentiated than human VFs. The special homogeneity of VF tissue along anterior–posterior direction was subject of pervious research (Dollinger et al, 2011; Kelleher et al, 2010). Similar to our results, point force excitations (Dollinger et al, 2011) showed that stiffness increases from the central region to the cartilaginous anterior– posterior ends for human tissue, in contrast with those of tensile test (Kelleher et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The special homogeneity of VF tissue along anterior–posterior direction was subject of pervious research (Dollinger et al, 2011; Kelleher et al, 2010). Similar to our results, point force excitations (Dollinger et al, 2011) showed that stiffness increases from the central region to the cartilaginous anterior– posterior ends for human tissue, in contrast with those of tensile test (Kelleher et al, 2010). Finite element models have shown that anisotropy affects the eigenfrequencies of VF tissue (Kelleher et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A hemilarynx setup was used to impose a map of static tensile point forces about 0.1-1 N over the superior surface of the human vocal folds. 55 After reconstruction of the 3D deformation field, the deformation-to-force ratio was determined. This ratio uniformly decreased from the posterior region to the anterior region, in contrast to what was found by the LSR study.…”
Section: Excised-larynx Testingmentioning
confidence: 99%
“…In addition to studying vocal fold properties and geometry, experiments are often performed to study the mechanics of vocal fold flow-induced vibration (e.g., [9, 10]). With respect to reliable measurement methods to determine these mechanics, reproducible specimens are needed that withstand several investigations without changes in their material properties.…”
Section: Introductionmentioning
confidence: 99%